Professor Molly Jahn on supporting people's food choices - Jahn, Molly M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Although food security for all is a widely-held goal, it has not been achieved. Professor Jahn (University of Madison-Wisconsin, USA) on bringing US experiences and perspectives to the work of the commission, and bringing the commission's work to the farming community, policymakers and consumers in the U.S.